EFFECT OF CHARACTERISTICS INFORMATION MANAGEMEN HOSPITALS ON PERFOMANCE MANAGERIAL IN ORTOPEDIC HOSPITAL PROF. DR. R. SOEHARSO SURAKARTA YEAR 2010 - Tri Hariyati; Sri Sugiarsi; Dwi Linna Suswardany (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2013)
ABSTRACTManagement information system (MIS) aims to provide support in the transaction processing atthe operational level and little support at the tactical level planning and management control. MIShas characteristics broadscope, aggregation, integration, timeliness, accuracy, and clarity serveto help pedict the possible consequences of various actions that can be done on perfomanceimprovement activities in an effective and efficient managers. The study was conducted todetermine the effect of information on the perfomance characteristic manajerial. Research typeused is analytical descriptive study with cross sectional design. Respondents used in this study isthe manager at the Hospital Ortopedic Prof. DR. R. Soeharso Surakarta. Data analysis consistedof descriptive and analytical analysis. The method used in analyzing the data is linear regressionanalysis with the help of the program Statistical Package for Social Science (SPSS) version 16.0.Results obtained by analysis of the Sig. F (0.00) < Sig of alpha (0.05). Which means there is aninfluence together all the characteristics of variable information (broadscope, aggregation,integration, timeliness, accuracy, and clarity) on managerial perfomance. Characteristicsinfluence the information on this research that is equal to 54.70%.Key words: characteristics of information, management information system, andmanagerial perfomance.